2015
DOI: 10.1001/jamasurg.2014.3171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laparoscopic Surgery on Health Care Utilization and Costs in Patients Who Undergo Colectomy

Abstract: Laparoscopic colectomy results in a significant reduction in health care costs and utilization in the short- and long-term postoperative periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…Our data supports a growing body of literature that minimally invasive procedures may be associated with increased OR cost but are potentially overall cost saving when other variables are considered [4, 15, 16]. This study corroborates those findings in that we also found that MIE was associated with longer and more expensive operations but was not associated with increased total hospital cost.…”
Section: Discussionsupporting
confidence: 91%
“…Our data supports a growing body of literature that minimally invasive procedures may be associated with increased OR cost but are potentially overall cost saving when other variables are considered [4, 15, 16]. This study corroborates those findings in that we also found that MIE was associated with longer and more expensive operations but was not associated with increased total hospital cost.…”
Section: Discussionsupporting
confidence: 91%
“…Both of these resource use variables may give rise to rare but extreme costs, which can influence the entire result of the study and single-handedly tip the result in one direction, especially if the study contains few patients as is the case here 15 . It was reported recently that patients who underwent open colectomy were absent from work on average 2⋅75 days more than those who had laparoscopic surgery 28 . Based on these results, if sick leave costs were included, it is likely that Hartmann's procedure would be even more costly than laparoscopic lavage.…”
Section: Discussionmentioning
confidence: 97%
“…Given that sample sizes were sufficient to summarize total visit cost for patients presenting with lead damage in the inpatient setting, we calculated the total hospitalization cost by summing the amount paid to the hospital by the insurer plus coinsurance, copayments, and deductibles paid by the patient. Given the distribution of total hospitalization costs observed, we excluded from cost analyses 19 patients whose total costs fell into the top 5% of the cohort (greater than $73 573 for the PM cohort, $191 042 for ICD, and $296 320 for the CRT‐D cohort) 9, 10, 11, 12. We hypothesized that these patients may have had other major procedures besides just lead revision or repair, resulting in the extreme variance in cost.…”
Section: Methodsmentioning
confidence: 99%